Cryptocurrency Invesment Analysis for Students in Makassar City - Hasma Fitrayanti; Muchriana Muchran (www.amertainstitute.com, 2024)
This study aims to analyze cryptocurrency investment among students in Makassar City, using the influence of knowledge variables about cryptocurrency and risk and security perceptions on the investment. This study applies a descriptive quantitative method, with data collection through a dichotomous scale questionnaire. Data analysis was carried out using SPSS Statistics 26, including the Guttman Scale Validity Test, Reliability Test, and data presentation in a frequency distribution table accompanied by a bar chart. The results showed that 30% of students with limited knowledge and high risk perceptions tend to avoid cryptocurrency investment and choose safer investments. As many as 24% of students with basic understanding and concerns about risk are still hesitant to invest in large amounts. Meanwhile, 45% of students with good knowledge and measurable risk perceptions are more daring to invest despite fluctuations and security risks. These findings suggest that better knowledge and more positive risk perceptions can increase participation in cryptocurrency investment.